KUPUNESIA APP FOR CITIZEN SCIENCE: NEW WAY OF MAINSTREAMING INTEREST AND STUDY OF INDONESIAN BUTTERFLIES - Djunijanti Peggie; Swiss Winasis Bagus Prabowo; Abdul Mutholib Shahroni; Fariq Izzudien Ash Shidiq; Lutfi Irwansyah; Soenarko Soenarko; Nabila Rahma; Imti Yazil Wafa (Treubia, 2022)
Indonesia is a mega biodiversity country and is host to many endemic butterfly species. However, data about Indonesian butterflies is still very limited due to some constraints of research personnel capacity, budget, challenging access to many islands, and other factors. This paper aims to inform a new direction using the Kupunesia App as a breakthrough and to invite more citizen science participation to accelerate butterfly research in Indonesia. The involvement of butterfly enthusiasts as citizen scientists has increased the knowledge as can be seen within one month of the launching of the App in November 2022. About 500 people have downloaded the App, 182 people have contributed their data to Kupunesia App, 342 checklists were recorded and 321 species were observed from various locations in Indonesia. This momentum should be maintained so that it can effectively and sustainably support citizen scientists.